2022
DOI: 10.1021/acs.chemmater.2c02162
|View full text |Cite
|
Sign up to set email alerts
|

Phase-Specific Vapor–Liquid–Solid Growth of GeSe and GeSe2 van der Waals Nanoribbons and Formation of GeSe–GeSe2 Heterostructures

Abstract: Group IV (Ge, Sn) chalcogenides differ from most other two-dimensional (2D)/layered semiconductors in their ability to crystallize both as stable mono- and dichalcogenides. The associated diversity in structure and properties presents the challenge of identifying conditions for the selective growth of the different crystalline phases, as well as opportunities for phase conversion and materials integration/interface formation in heterostructures. Here, we discuss the phase-selective synthesis of free-standing G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…GeSe-based TFSCs devices could experience adverse effects on their performance if GeSe 2 is formed in GeSe absorbing layer because GeSe 2 is a p-type semiconductor with a relatively wide E g of %2.7 eV. In an interesting study, Yumigeta et al [61] synthesized the nanostructures including GeSe and GeSe 2 via CVD method using halide-based precursors at atmospheric pressure and 400 °C temperature. By analyzing various physicochemical properties combined with a thorough analysis of CVD experiments, authors have concluded that the resulting stoichiometry and phase of GeSe and GeSe 2 nanosized materials are determined by several factors, including substrate temperature, selenium partial pressure, and the type of substrates used.…”
Section: Preparation Process For the High-quality Gese Thin Filmsmentioning
confidence: 99%
“…GeSe-based TFSCs devices could experience adverse effects on their performance if GeSe 2 is formed in GeSe absorbing layer because GeSe 2 is a p-type semiconductor with a relatively wide E g of %2.7 eV. In an interesting study, Yumigeta et al [61] synthesized the nanostructures including GeSe and GeSe 2 via CVD method using halide-based precursors at atmospheric pressure and 400 °C temperature. By analyzing various physicochemical properties combined with a thorough analysis of CVD experiments, authors have concluded that the resulting stoichiometry and phase of GeSe and GeSe 2 nanosized materials are determined by several factors, including substrate temperature, selenium partial pressure, and the type of substrates used.…”
Section: Preparation Process For the High-quality Gese Thin Filmsmentioning
confidence: 99%
“…25,26 This approach inherently increases production cost due to the necessity of maintaining high-vacuum background and often suffers from a slow growth rate, 27 with growth variables closely tied to specific system geometries. In contrast, the tube furnace system offers versatility for the cost-effective growth of lowdimensional crystalline materials, such as 1D nanowires, 28,29 2D materials, 30,31 and thin films. 32,33 With its capacity for high quality and yield, 23 the tube furnace stands out as a more suitable option for potential scale-up processes, such as continuous roll-to-roll processing on a large-area substrate.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This is because the morphology of MHP crystals, including attributes such as grain size and film thickness, fundamentally dictates their carrier generation and transport properties, and hence, their overall optoelectronic performance. ,, While prior reports on vapor deposition of MHPs have emphasized their potential for large-area film growth, , the majority employ direct source evaporation onto a substrate in a vacuum chamber. , This approach inherently increases production cost due to the necessity of maintaining high-vacuum background and often suffers from a slow growth rate, with growth variables closely tied to specific system geometries. In contrast, the tube furnace system offers versatility for the cost-effective growth of low-dimensional crystalline materials, such as 1D nanowires, , 2D materials, , and thin films. , With its capacity for high quality and yield, the tube furnace stands out as a more suitable option for potential scale-up processes, such as continuous roll-to-roll processing on a large-area substrate . Despite this, ensuring spatially uniform films in such a system is challenging due to the uncontrollable precursor concentration and spatially nonuniform growth kinetics.…”
Section: Introductionmentioning
confidence: 99%